A Brief History of Insecticides and Quail - Amanda Gobeli; Caitlin Thompson; Kelly S. Reyna (National Quail Symposium Proceedings, 2017)
Humans have employed chemical methods of pest control since the earliest days of agriculture and these substances have affected native wildlife, including quail and other gamebirds (Galliformes), to varying degrees. Several quail species have experienced steep population declines over the past several decades and insecticides may be a contributing factor. Quail are also known to use agricultural habitat for nesting and foraging purposes and are therefore likely to encounter elevated levels of insecticidal chemicals in the soil, vegetation, and insect biomass in that environment. The first commercially available insecticides appeared in the early 1900s with the introduction of arsenic-based compounds (arsenicals). Chemical engineering during World War II resulted in arsenicals being replaced with synthetically produced insecticides such as organochlorine, carbamate, and organophosphate compounds over several decades. Many of these substances have been shown to increase mortality rate, alter behavior, and produce severe reproductive complications in quail, both in the lab and the field. Today, the world’s most popular insecticides, neonicotinoids, are being reevaluated for environmental safety following reports that they may be affecting nontarget wildlife. This review examines the types of insecticides that have been used in the United States, how quail could be exposed to these substances, and how they may have contributed to declining quail populations.
Keywords: colinus virginianus; northern bobwhite; arsenicals; carbamates; insecticides; neonicotinoids; organochlorines; organophosphates; pesticides; quail